Effect of pre-confining pressure on unloading-induced coalburst: Insights from distinct element modelling - Cao, Jinrong; Dou, Linming; Zhou, Kunyou; Kan, Jiliang; Li, Jiazhuo; Chai, Yanjiang (Frontiers in Earth Science, 2023)
Coalburst is a violent dynamic failure of coal during underground mining. It is of significance to study failure pattern as well as energy evolution and transition during coalbursts and how they are influenced by pre-confinement. This paper presents unloading-induced coalburst simulations using the distinct element method (DEM) via a combined static–dynamic loading–unloading strategy. The numerical model is calibrated and validated by comparison with the failure process observed in laboratory tests. The influence of pre-confining pressure on unloading-induced coalburst was numerically investigated from the perspective of crack propagation, fracturing process, failure pattern, and energy evolution. In addition, failure mechanism and energy conversion during coalbursts under different pre-confining pressures are discussed. The results show that the stress change caused by sudden unloading of the pre-confining results in the initiation and development of cracks. Crack density and crack propagation velocity increase with increasing pre-confining pressure. As the pre-confining pressure increases, the coalburst becomes more intense and takes less time to be completed, and the main failure pattern in coalburst transforms from a tensile type to a shear type. In addition, the conversion ratio of kinetic energy and frictional energy during coalbursts increase nonlinearly with increasing pre-confining pressure.